(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
Postures oriented by ethical and moral values are valued by society and by the labor market, but they are not followed absolutely. Given the frequency with which fraud involving unethical conduct of accounting professionals is reported, this research contributes to the deepening of this discussion about ethics, and encompasses the initial phase of career, professional education, advancing in the characterization of the ethical profile of accounting professionals and intensifying the ethical awareness in students and accounting professionals. The present study has the objective of analyzing the students’ perception of the professional ethics, considering certain intervening variables related to individual factors. The research method used is classified as quantitative, descriptive and survey, with the application of a closed questionnaire. The sample represents 214 students from the Federal University of Santa Catarina. The data were analyzed with the aid of the nonparametric tests of Spearman and Kruskal-Wallis, post-hoc Dunn- Bonferroni. The results indicate that the individual factors influence significantly in the students’ point of view about the professional ethics and that the discipline Ethics and Political Philosophy in the course of Accounting tends to make the students aware of the responsibilities and behaviors that must be followed by the accounting professionals. Therefore, the individual factors added to ethical education induce in a relevant way the ethical attitudes of the students. However, this statement deals only with the sample analysis of this study, because differences were found when comparing this study with the results of the literature.